Implementation of the Program for Strengthening Religious Moderation in Aceh Madrasas - Hadini Hadini; M. Imamuddin; Charles Charles; Isnaniah Isnaniah; Nurbayani Nurbayani; Ressy Kurniasari (AL-ISHLAH: Jurnal Pendidikan, 2024)
Educational institutions play a critical role in fostering religious moderation, aiming to cultivate future generations with balanced attitudes and thoughts. This study investigates the understanding and awareness of religious moderation among students at MAN 4 Aceh Besar and explores the programs designed to strengthen this concept. Additionally, it examines the factors that support or hinder the success of these programs. A mixed-methods approach was employed, integrating qualitative and quantitative techniques. Data were collected through observation, interviews, documentation, and scales. Quantitative data analysis determined the level of student understanding, while qualitative methods provided insights into program implementation and influencing factors. Findings reveal that students at MAN 4 Aceh Besar demonstrate an 80.8% understanding and awareness of religious moderation, categorizing the institution as successful in supporting its objectives. Religious moderation programs are integrated into both teaching materials and extracurricular activities, ensuring a holistic approach. Supporting factors for the program's success include moral and material backing from stakeholders. However, challenges arise from both internal and external influences, which may limit the program's effectiveness. The religious moderation program at MAN 4 Aceh Besar has effectively fostered student awareness and understanding, demonstrating the institution's commitment to cultivating moderate perspectives. Continuous support and strategic interventions are necessary to address the identified challenges and sustain progress.